A Study of Female Entrepreneurs in Belize - Aldana, Gerson; Thiagarajan, Somanadevi (Asian Journal of Social Sciences and Management Studies, 2016)
A research was carried out to understand, analyze and document the profile of female entrepreneurs in Belize and to identify the factors that contribute to their success. The data was collected through questionnaires and analyzed by using SPSS. The profile studied include age, education level, income, number of children, marital status, business type, etc. The factors that contribute for success of the female entrepreneurs were measured by using variables such as profits, social status, self-achievement, quality of product and services. To improve success and life style it is recommended that the female entrepreneurs engage in continuous training and complete tertiary level education. In order to encourage more women to become entrepreneurs, financial institutions should create micro financing outlets to provide credit facilities along with sound business and legal advice.